# Factorize the following equation:

\[{\text{ }}{x^3} - 5{x^2} - 2x + 24\]

Answer

Verified

364.8k+ views

Hint: Put the different values of $x$ in the given equation until the value of the equation becomes zero.

We have to find such value which will make the whole expression equal to zero

Such that

$P(x) = {x^3} - 5{x^2} - 2x + 24$

Let $x = 1$, we get,

$P(1) = {(1)^3} - 5{(1)^2} - 2(1) + 24$

$P(1) = 1 - 5 - 2 + 24 = 13 \ne 0$

Now, let ${\text{ }}x = 2$

$P(2) = {(2)^3} - 5{(2)^2} - 2(2) + 24$

$P(2) = 8 - 20 - 4 + 24 = 8 \ne 0$

Now, let${\text{ }}x = - 2$

$P( - 2) = {( - 2)^3} - 5{( - 2)^2} - 2( - 2) + 24$

$P( - 2) = - 8 - 20 + 4 + 24 = 0$

Since the value comes out to be zero,

Therefore, \[x + 2\]is one of the factors.

The other factors can be calculated by dividing the given expression

${x^3} - 5{x^2} - 2x + 24{\text{ by }}x + 2.$

That is,

${\text{(}}{x^3} - 5{x^2} - 2x + 24) \div {\text{(}}x + 2)$

$\begin{gathered}

{\text{ }}{x^2} - 7x + 12 \\

x + 2\left){\vphantom{1{{x^3} - 5{x^2} - 2x + 24}}}\right.

\!\!\!\!\overline{\,\,\,\vphantom 1{{{x^3} - 5{x^2} - 2x + 24}}} \\

{\text{ }}{x^3} + 2{x^2} \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ - 7}}{x^2} - 2x + 24 \\

{\text{ - 7}}{x^2} - 14x \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ 1}}2x + 24 \\

{\text{ 1}}2x + 24 \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ 0}} \\

\end{gathered} $

Thus, we get, the other factor as ${x^2} - 7x + 12$

Which can be written as

\[ = {x^2} - 4x - 3x + 12\]

$ = x(x - 4) - 3(x - 4)$

$ = (x - 3)(x - 4)$

Hence, the required solution: ${\text{(}}{x^3} - 5{x^2} - 2x + 24) = (x + 2)(x - 3)(x - 4)$

Note: The first factor must be chosen very carefully as the other factors are determined on its basis only. Later we have the divide the cubic equation by the first factor to convert it into a quadratic equation and factorised to find the remaining factors.

We have to find such value which will make the whole expression equal to zero

Such that

$P(x) = {x^3} - 5{x^2} - 2x + 24$

Let $x = 1$, we get,

$P(1) = {(1)^3} - 5{(1)^2} - 2(1) + 24$

$P(1) = 1 - 5 - 2 + 24 = 13 \ne 0$

Now, let ${\text{ }}x = 2$

$P(2) = {(2)^3} - 5{(2)^2} - 2(2) + 24$

$P(2) = 8 - 20 - 4 + 24 = 8 \ne 0$

Now, let${\text{ }}x = - 2$

$P( - 2) = {( - 2)^3} - 5{( - 2)^2} - 2( - 2) + 24$

$P( - 2) = - 8 - 20 + 4 + 24 = 0$

Since the value comes out to be zero,

Therefore, \[x + 2\]is one of the factors.

The other factors can be calculated by dividing the given expression

${x^3} - 5{x^2} - 2x + 24{\text{ by }}x + 2.$

That is,

${\text{(}}{x^3} - 5{x^2} - 2x + 24) \div {\text{(}}x + 2)$

$\begin{gathered}

{\text{ }}{x^2} - 7x + 12 \\

x + 2\left){\vphantom{1{{x^3} - 5{x^2} - 2x + 24}}}\right.

\!\!\!\!\overline{\,\,\,\vphantom 1{{{x^3} - 5{x^2} - 2x + 24}}} \\

{\text{ }}{x^3} + 2{x^2} \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ - 7}}{x^2} - 2x + 24 \\

{\text{ - 7}}{x^2} - 14x \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ 1}}2x + 24 \\

{\text{ 1}}2x + 24 \\

\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_ \\

{\text{ 0}} \\

\end{gathered} $

Thus, we get, the other factor as ${x^2} - 7x + 12$

Which can be written as

\[ = {x^2} - 4x - 3x + 12\]

$ = x(x - 4) - 3(x - 4)$

$ = (x - 3)(x - 4)$

Hence, the required solution: ${\text{(}}{x^3} - 5{x^2} - 2x + 24) = (x + 2)(x - 3)(x - 4)$

Note: The first factor must be chosen very carefully as the other factors are determined on its basis only. Later we have the divide the cubic equation by the first factor to convert it into a quadratic equation and factorised to find the remaining factors.

Last updated date: 02nd Oct 2023

â€¢

Total views: 364.8k

â€¢

Views today: 8.64k

Recently Updated Pages

What do you mean by public facilities

Please Write an Essay on Disaster Management

Paragraph on Friendship

Slogan on Noise Pollution

Disadvantages of Advertising

Prepare a Pocket Guide on First Aid for your School

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

One cusec is equal to how many liters class 8 maths CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE